REPORT OF THE ANNUAL CONVENTION. - Cox, R. C. (The Accounting Review, 1956)
Abstract The 1935 annual meeting of the American Accounting Association was one of the most successful and enjoyable in its history. It was held on August 30, 31, and September 1, in Philadelphia, Pennsylvania, with the Wharton School of Finance and Commerce, University of Pennsylvania, as host. A motion was made from the floor and carried accepting the report of the Committee on Nominations and instructing the Secretary Treasurer to cast a unanimous ballot for election of the above named persons. One of the most interesting aspects of the convention was the plant visitation to the Fairless Works of U.S. Steel on Friday, September 2. About 110 members of the association visited the Fairless Works, making a complete tour of the plant in the normal production sequence. The Fairless Works is a fully integrated steel producing plant from the coking of coal through the production of finished hot- and cold-rolled sheets, bar mill and tin mill products. Among the products produced at the Fairless Works are carbon high-strength and alloy steel ingots, blooms, billets, slabs bars, hot- and cold-rolled sheets, black plates, and electrolytic coated tinplate.